Engineering Mathematics in Ship Design - Dos Santos, Elizaldo Domingues; Djordjevic, Nenad; Fragassa, Cristiano (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Engineering mathematics is a branch of applied mathematics where mathematical methods and techniques are implemented for solving problems related to the engineering and industry. It also represents a multidisciplinary approach where theoretical and practical aspects are deeply merged with the aim at obtaining optimized solutions. In line with that, the present Special Issue, 'Engineering Mathematics in Ship Design', is focused, in particular, with the use of this sort of engineering science in the design of ships and vessels. Articles are welcome when applied science or computation science in ship design represent the core of the discussion.
English
Keywords: Lead-Zirconium-Titanium (PZT); n/a; H.O.M.E.R. nozzle; finite element; low-speed Diesel engine; piezoelectric sensor; AHP method; environmental management system; SPH; state-of-the-art; marine transport; single-stepped planing hulls; optimisation; finite element method; computational fluid dynamic; slamming; FSI; roll motion; harmonic excitation; external forces; towing tank tests; modelling; roll damping; ISO 9126; selection; stiffened plate; numerical model; damaged sensor; CFD; symmetric 2D + T theory; hydroelasticity; ISO 14001; water entry; plate; constitutive model; turbulence model; SHIPMOVE; impact traction; fixed pitch propeller; stiffeners; numerical simulation; cavitation; controllable pitch propeller; ISO 14598; MMG Model; hydrodynamic forces; balanced scorecard; finite volume method; deflection; constructal design; fluid-structure interaction; MCDM method; marine industry; ship design; fracture mechanics; coanda effect